Harmonic mitigation in an islanded microgrid using a DSTATCOM - Goyal, M.; John, B.; Ghosh, Arindam (2016)
The degree of proliferation of Distributed Energy Resources (DERs) and application of power electronics appliances are in demand. A microgrid can contain variety of sources such as diesel generator, wind turbine, PV arrays, micro-turbine and fuel cell. Usually these sources share power where the system frequency changes depending on the power supplied. On the other hand, the microgrid can contain harmonic loads that can affect the performance of the synchronous generators. These deleterious effects of distorting loads can be corrected using a distribution static compensator (DSTATCOM). In this paper, an isochronous control based droop strategy is employed that forces the microgrid to operate at the base frequency of 50 Hz. Therefore the DSTATCOM can be operated at 50 Hz. A closed-loop space vector pulse width modulation (SVPWM) technique is used for the DSTATCOM control. The scheme is validated through the extensive PSCAD/EMTDC simulation studies.